A new strategy for synthesis of lithium zinc titanate as an anode material for lithium ion batteries. (20th March 2015) - Chen, Baokuan; Du, Chaojun; Zhang, Yezhen; Sun, Ruixue; Zhou, Li; Wang, Lijuan
Highlights: Li2 ZnTi3 O8 has been firstly synthesized via a molten-salt method. Li2 ZnTi3 O8 can be synthesized by sintering for only 1 h via molten-salt method. Li2 ZnTi3 O8 delivers large specific capacities. Abstract: Lithium zinc titanate (Li2 ZnTi3 O8 ) anode materials have been firstly synthesized via a molten-salt method using 0.38LiOH·H2 O–0.62LiNO3 as eutectic molten salts. The effects of sintering temperature and sintering time on the structures and physicochemical properties of the Li2 ZnTi3 O8 materials are also studied in detail. It is found that Li2 ZnTi3 O8 obtained by sintering at 700 °C for 3 h exhibits a typical cubic spinel structure with P43 32 space group. Nano-sized particles are presented and the particles are homogeneous for the Li2 ZnTi3 O8 prepared by sintering at 700 °C for 3 h. Electrochemical tests demonstrate that the sample possesses large capacities. The largest capacities of 167.8 and 142.4 mAh g −1 are delivered at 2 and 3 A g −1, respectively. 137.8 and 113.3 mAh g −1 are kept for the sample at the 100th cycle at the two current densities, respectively. The large discharge specific capacities may be attributed to the good crystallinity, small particle size and low charge-transfer resistance of Li2 ZnTi3 O8 .